Distributional preferences and donation behavior among marine resource users in Wakatobi, Indonesia - Katherine M. Nelson; Achim Schlüter; Colin Vance (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
This study examines the effect of participants' distributional preferences on donations of money and time using a field experiment with marine resource users in Indonesia. Individuals participate in a real effort task to earn money and are faced with a donation decision under different treatments - monetary donation, time donation, monetary match, and time match. In the distributional preferences elicitation we classify individuals' preferences as benevolent, egalitarian, own-money-maximizing, and spiteful. We find that the different distributional preference types are a significant indicator of participants' donation behavior. The people showing spiteful preferences and those that focus only on maximizing their own payoff are less likely to donate any amount compared to those that make egalitarian choices. Furthermore, we find strong evidence that individuals that choose payoff structures characterized as "benevolent" donate a significantly higher amount compared to the egalitarian types. We analyze the results econometrically in two-stages to better understand the determining factors for whether an individual donates and those factors that determine how much one donates. Practical implications involve the segmentation of the target audience, not by the type of charity but by the mechanism which motivates their donation behavior. – – Diese Studie untersucht die Auswirkungen von Verteilungspräferenzen auf Geld- und Zeit-Spenden in einem Feldexperiment mit marinen Ressourcennutzern in Indonesien. Alle Teilnehmenden müssen zunächst eine einfache Arbeit verrichten. In der ersten Versuchsgruppe müssen sie im Anschluss der Arbeit entscheiden, welchen Anteil des verdienten Geldes sie gerne spenden möchten. In der zweiten Gruppe entscheiden sie kontinuierlich während der Arbeit, ob sie gerade für sich oder für den guten Zweck arbeiten wollen. Zwei weitere Versuchsgruppen bekommen jeweils eine Verdoppelung durch den Experimentator der Zeit- oder Geldspenden. Mit Hilfe monetärer Anreize erheben wir Verteilungspräferenzen und klassifizieren die Teilnehmer als wohlwollend, egalitär, eigennutzmaximierend und gehässig. Wir zeigen, dass die verschiedenen Verteilungspräferenzen ein wichtiger Indikator für das Spendenverhalten der Teilnehmer sind. "Gehässige" und "eigennutzorientierte" Menschen spenden signifikant weniger als "egalitäre" Menschen. "Wohlwollende" Menschen geben deutlich jedoch nicht signifikant mehr als "egalitäre". Die Daten werden mit einem zweistufigen ökonometrischen Verfahren analysiert, um zu verstehen, welche Charakteristika, dazu führen, dass eine Person spendet bzw. mehr spendet. Die Ergebnisse deuten darauf hin, dass eine Zielgruppe für Spendenkampagnen nicht zwangsläufig nach der Spendenorganisation ausgewählt werden sollte, sondern nach den Charakteristika des Spendenden.
Keywords: Q22; Z1; 330; distributional preferences; donations; field experiment